The double-edged sword of internet use in China’s aging population: thresholds, mediation and digital health policy - Li, Yirong; Cai, Jianguang; Yu, Haiyong (Frontiers in Public Health, 2025)
BackgroundAmid global aging and digital transformation, the dual effects of Internet use on health—its potential benefits and risks—remain a subject of debate. This study investigates the threshold effects of Internet use, the mediating role of physical activity, and the implications for digital health policy in China, revealing a compensation-vulnerability paradox among disadvantaged groups.MethodsThe data were drawn from the 2020 China Family Panel Studies (CFPS), a nationally representative sample comprising 7,308 adults aged ≥45. We conducted multivariable regression with robustness checks and bootstrap mediation analysis. Nonlinear sensitivity was tested via U-shaped relationship validation and threshold effect identification.ResultsModerate Internet use (below 4.8 h/day) confers health benefits, but excessive use leads to adverse outcomes. Physical activity serves as a partial mediator in this relationship, exhibiting nonlinear mediation dynamics. Although the current average of 1.8 h/day of use internet is well below the harmful threshold, structural digital exclusion creates a compensation-vulnerability paradox: older and less-educated groups derive greater marginal health benefits from moderate use but face higher risks of overuse due to limited digital literacy and physiological constraints.ConclusionInternet use offers conditional health benefits for older adults, contingent on usage thresholds and mediated by physical activity. Policymakers must balance targeted digital inclusion with safeguards against overuse, particularly for vulnerable groups. These findings highlight the need for time-bound digital health interventions and literacy programs to address the paradox of technological compensation and vulnerability, informing digital health policy in aging societies.